The spanish Royal House in X (Twitter): Towards the public positioning of the Princess of Asturias - Panizo Alonso, Julio Manuel; Pulido Polo, Marta; Vázquez-González, José (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The main objective of this work is to determine the digital communication style of the Spanish Royal House in relation to the progressive public positioning of the Princess of Asturias as heir to the Crown of Spain. A multivariate quantitative analysis (content analysis) is carried out in SPSS (Krippendorff alpha coefficient = 0.867) on a corpus of 948 tweets issued by the X @CasaReal account between January 1 and December 31, 2023. consolidates itself as a relevant relationship management tool for the public positioning of the Princess of Asturias.